The Use of Discourse Markers in narrative by Chinese speakers of L2 European Portuguese - He, Liuyang; Li, Qinxue; Yang, Aoran (Orientes do Português, 2023)
In an attempt to examine the use of discourse makers by Chinese speakers of Second Language (L2) European Portuguese (EP) in oral narrative production, the current study is oriented by two research questions: (1) how is the frequency, distribution and variety of the discourse makers used by Chinese speakers of L2 EP? (2) is L2 proficiency level a potential factor that affects the use of discourse markers in narrative? On the basis of quantitative and qualitative analysis on the empirical data collected from 13 Chinese learners of EP, the results reveal that learners at a higher L2 level tend to produce more discourse markers in narrative, especially the structuring discourse markers. However, when it comes to the variety and distribution of this linguistic term, it seems that the richness of discourse markers does not correlate positively with L2 level and that almost all these expressions occur in the sentence-initial position.